Are Expectations Alone Enough? Estimating the Effect of a Mandatory College-Prep Curriculum in Michigan - Brian A. Jacob; Susan M. Dynarski; Kenneth Frank; Barbara Schneider (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper examines the impacts of the Michigan Merit Curriculum (MMC), a statewide college-preparatory curriculum that applies to the high school graduating class of 2008 and later. We use a student, longitudinal database for all public school students in Michigan for the main analyses, and complement this with analyses from a state-year panel. The study employs several non-experimental approaches, including a comparative interrupted time series and a synthetic control method. Our analyses suggest that the higher expectations embodied in the MMC has had little impact on student outcomes. Looking at student performance on the ACT, the only clear evidence of a change in academic performance comes in science. Our best estimates indicate that ACT science scores improved by 0.2 points (or roughly 0.04 standard deviations) as a result of the MMC. Students who entered high school with the weakest academic preparation saw the largest improvement, gaining 0.35 points (0.15 standard deviations) on the ACT composite score and 0.73 points (0.22 standard deviations) on the ACT science score. Our estimates for high school completion are very sensitive to the sample and methodology used. Some analysis suggests a small negative impact on high school graduation for students who entered high school with the weakest academic preparation, but other analysis finds no such effect.
Keywords: 330; college-preparatory curriculum; comparative interrupted time series; synthetic control